Role of community colleges and other TVET institutions in advancing sustainable development by supporting access, diversity, and inclusion for nontraditional student populations - Raby, R.L.; Legusov, O.; Addae, D.; et al. (Diaspora, Indigenous, and Minority Education, 2023)
The Sustainable Development Goals link access to higher education, parti cularly for non-traditional populations, as a way to fight poverty and ensure prosperity. This article examines the experiences of several under-researched categories of non-traditional students who attend Community Colleges and Technical Vocational Education and Training (TVET) Colleges in multiple jurisdictions worldwide. The article begins to fill in the gap with comparative data on how these institutions advance equity, diversity, and inclusion through access to higher education. The implications of Community Colleges and TVET are analyzed using the lens of Neo-Liberalism and the Capabilities Narrative. The study extends the scope of the inquiry into the contributions these institutions make to sustainable development. The arti cle uses a comparative multi-case study approach to examine the Community Colleges and TVET Colleges in different jurisdictions worldwide.
Research Article
Keywords: Sustainable development; TVET; community colleges